2009
DOI: 10.1007/s00018-009-0056-9
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin

Abstract: Autotaxin is a protein of approximately 900 amino acids discovered in the early 1990s. Over the past 15 years, a strong association between cancer cells and autotaxin production has been observed. Recent publications indicate that autotaxin and the capacity of cancer to metastasise are intimately linked. The discovery of new molecular targets in pharmacology is a mixture of pure luck, hard work and industrial strategy. Despite a crucial and desperate need for new therapeutic tools, many targets are approached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 131 publications
(137 reference statements)
2
31
0
Order By: Relevance
“…Bronchial epithelial cells as well as inflammatory macrophages showed the highest expression of autotaxin found in the aforementioned BALFs. Genetic depletion of autotaxin in bronchial epithelial cells and bronchial macrophages resulted in decreased disease severity [20]. In our study, we found that not only is ENPP-2 up-regulated in pulmonary NKT cells after hyperoxia, but that the downstream product LPA also increases after hyperoxic injury.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Bronchial epithelial cells as well as inflammatory macrophages showed the highest expression of autotaxin found in the aforementioned BALFs. Genetic depletion of autotaxin in bronchial epithelial cells and bronchial macrophages resulted in decreased disease severity [20]. In our study, we found that not only is ENPP-2 up-regulated in pulmonary NKT cells after hyperoxia, but that the downstream product LPA also increases after hyperoxic injury.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, we demonstrated up-regulation of ENPP-2 (autotaxin) on pulmonary NKT cells in response to hyperoxia. Autotaxin shows a broad tissue distribution in adult mice with high mRNA levels in the lung [20]. Increased autotaxin levels have been demonstrated in other disease models and could be found in synovial fluid of arthritis patients as well as human astrocytes following brain injury suggesting its role in inflammation [21].…”
Section: Discussionmentioning
confidence: 99%
“…The multiple biological functions of NPP2 (autotaxin) are now mainly attributed to its phospholipase D activity and include promotion of cancer cell invasion, cell migration, lymphocyte trafficking, and angiogenesis [343][344][345]. A brainspecific variant (PD-Iα/ATXγ) is found almost exclusively on the myelin forming oligodendrocytes of the brain [346].…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…The ENPP2 gene contains 27 exons with a considerable number of potential alternative splicing sites. Three different isoforms have been characterized that differ in length and tissue distribution [344,406]. The nomenclature of the isoforms varies between authors [343,344,348,406].…”
Section: General Molecular Propertiesmentioning
confidence: 99%
See 1 more Smart Citation